PENGARUH GENDER DAN PERSEPSI TINDAKAN KORUPSI TERHADAP NIAT MELAKUKAN PENYELEWENGAN PAJAK - Dewi Kusuma Wardani; Danis Tri Hastuti Istiani (Bajang Institute, 2022)
The study aims to examine effect of gender and perception of corruption in intention to commit tax fraud. The independent variable in this research are gender and perception of corruption while its dependent variable of intention to commit tax fraud. Sample in this research is Students Majors Accountancy at Sarjanawiyata Tamansiswa Yogyakarta University. The sample in this study is determined by sampling convenience method, the data collected with the distribution of questionnaires. The method of analysis used is double linear regresi analysis with IBM SPSS Statistics 20. Based on the result of the analysis indicate that gender has no influenceon intention to commit tax fraud and perception corruption has positif on intention to commit tax fraud.